Enablers and barriers of Adopting BI-tool for data analytics in Large Enterprises of Bangladesh - Khanom Konika; Nahid Mehzabul Hoque; Rabbani Golam Mustafa Md. Nurullah (SHS Web of Conferences)
The objective of this research is to examine the factors that facilitate or hinder the incorporation of Business Intelligence (BI) tools for data analysis and decision-making in enterprises in Bangladesh, using an adapted TOE framework. A quantitative methodology was used, consisting of a purposive survey conducted on 290 individuals who had experience in BI-Applications for the purpose of analytics. 191 valid survey responses were collected and analyzed using PLS-SEM. A conceptual framework consisting of 8 first order reflective constructs and 3 second order constructs were developed to examine the hypotheses, which portrays the main reflective elements as a set of variables that serve as reflective indicators for second-order constructs, encompassing technical, organizational, and environmental factors. The reported data indicated that factors such as relative advantage, compatibility, simplicity, top management support, organizational fit, competitive pressure, and vendor support have a substantial effect on the adoption of BI tools